Comparative analysis of mental health in middle-aged women with type-2 diabetes mellitus and hypothyroidism: A cross-sectional study - Rabia Aziz; Sohrab Ahmad Khan; Sumbul Ansari; Firdaus Jawed (Clinical Epidemiology and Global Health)
Background: Non-communicable diseases like hypothyroidism and type-2 diabetes mellitus are becoming increasingly prevalent and can lead to anxiety, depression, and memory problems. These mental health comorbidities often go undiagnosed despite significantly impacting quality of life. Sex differences are also observed, with women experiencing higher rates of both conditions. Objectives: This study aimed to compare the levels of anxiety, depression, and memory in middle-aged women with hypothyroidism and type-2 diabetes mellitus. Methods: This cross-sectional design recruited 243 females from Hakeem Abdul Hameed Catenary Hospital in New Delhi. Participants were divided into hypothyroidism and type-2 diabetes mellitus groups based on confirmed diagnoses. Questionnaires were used to assess anxiety (GAD-7), depression (PHQ-9), and memory (PGI-memory). Data analysis employed independent-sample t-tests and chi-square tests. Results: Significant differences (p < 0.05) emerged in mean mental health scores. The hypothyroidism group displayed higher anxiety (p < 0.05) and better memory (p < 0.05), while the diabetic group exhibited higher depression (p < 0.05). Results showed a higher prevalence of severe anxiety and depression in the diabetic group compared to the hypothyroidism group. Notably, the diabetic group also showed a significantly higher proportion of participants with moderate memory problems. Conclusions: This study suggests that both hypothyroidism and type-2 diabetes mellitus can impact mental health in middle-aged women. Type-2 diabetes mellitus appears to be associated with a greater prevalence of severe category of anxiety and depression, and with greater individuals in the moderate memory level category. These findings highlight the importance of comprehensive assessments to identify and address mental health comorbidities in patients with these chronic conditions.